A frog-inspired robot based on liquid-vapor phase transition - Endong Xiao; Weihao Zeng; Hantao Zhang; Wenkai Huang; Yetian Wang; Weicheng Kong; Pengcheng Zhang; Junfeng Zhao; Jing Zhu (Materials & Design)
Underwater robotics holds significant potential for marine exploration and ecological monitoring, yet conventional systems often face challenges such as noise, structural complexity, and limited adaptability. To address these limitations, this study presents a frog-inspired underwater robot driven by liquid–vapor phase transition technology, designed to emulate the agility and efficiency of biological locomotion. By leveraging the reversible volume change of low-boiling-point phase transition materials (HFO-1336mzz-Z), we developed a lightweight actuator system (≤ 7 g) capable of rapid response (≤0.5 s), high deformation (≥ 120°), and biomimetic flexibility. The robot integrates antagonistic leg mechanisms for dynamic propulsion, frog-inspired webbed feet for enhanced thrust-to-drag ratios (≈ 3), and thermochromic coatings for adaptive camouflage. Experimental results demonstrate a maximum joint angle change of 148°, an angular velocity of 0.88 rad/s, and a maximum propulsion speed of 127 mm/s. Furthermore, the robot successfully completes an ascent of 23 cm within 20 s. This compact, low-cost design overcomes traditional rigid or fluid-driven constraints, offering a novel framework for applications in underwater exploration, environmental sensing, and biomimetic research.